Adherence to Anti‐estrogen Therapy in Seniors with Breast Cancer: How Well are we Doing?. Issue 6 (23rd September 2014) - Trabulsi, Nora; Riedel, Kristen; Winslade, Nancy; Gregoire, Jean‐Pierre; Meterissian, Sarkis; Abrahamovicz, Michal; Tamblyn, Robyn; Mayo, Nancy; Meguerditchian, Ari
Abstract A third of breast cancers (BC) occur in women ≥65 years (seniors). Anti‐estrogen therapy (AET) significantly reduces BC recurrence and death. This study characterizes determinants of adherence to AET in seniors with BC. Provincial cancer registry and administrative claims data were accessed for all non‐metastatic BC diagnosed in Quebec (1998–2005) to identify seniors treated for 5 years with AET. Multivariate linear regression was used to assess the association with patient, disease, and physician characteristics and the 5‐year medication possession ratio (MPR) for each patient. 4, 715 women were included (mean age: 72.9). Mean MPR was 83.5%, 79% of patients reached a 5‐year MPR of ≥80%, and 34% discontinued AET at some point during treatment. The cumulative probability of discontinuation was 33.8% (mean time to discontinuation 2.3 years). The MPR decreased with increasing age and non‐BC related hospitalizations, p < 0.05. Each new medication added during the 5‐years decreased the MPR by 0.3% (p < 0.05). Women with in situ disease, on antidepressants at baseline, or treated with Tamoxifen had a lower MPR by 6.5% (p = 0.0002), 4.7% (p = 0.003) and 6% (p = 0.001), respectively. Switching AET type was associated with a lower MPR by 5.3% (p = 0.002) if the switch occurred during the first year. Optimal 5‐year adherence to AET in seniors with BC remained a challenge and medication discontinuation rates were high. Advanced age, increasing number of hospitalizations, in situ disease, baseline use of antidepressants, Tamoxifen (versus aromatase inhibitors), early switches of AET type, and newly added medications significantly reduced the MPR.